2020
DOI: 10.1016/j.medj.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Hydroxychloroquine Usage in United States Veterans Hospitalized with COVID-19

Abstract: Background: Despite limited and conflicting evidence, hydroxychloroquine, alone or in combination with azithromycin, is widely used in COVID-19 therapy. Methods: We performed a retrospective study of electronic health records of patients hospitalized with confirmed SARS-CoV-2 infection in US Veterans Health Administration medical centers between March 9, 2020 and April 29, 2020. Patients hospitalized within 24 h of diagnosis were classified based on their exposure to hydroxychloroquine alone (HC) or with azith… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
526
3
27

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(574 citation statements)
references
References 30 publications
8
526
3
27
Order By: Relevance
“…In another study, HCQ showed signi cant improvement in symptoms and radiological CT scan ndings [22] . One recent non-randomized study failed to demonstrate a bene t among patients hospitalized with an oxygen requirement A retrospective analysis of data from patients hospitalized with con rmed SARS-CoV-2 infection in all U.S. Veterans Health Administration medical centers until April 11, 2020 concluded that no clear evidence that the use of HCQ, either with or without azithromycin, reduced the risk of mechanical ventilation in patients hospitalized with COVID-19 [25]. An association of increased overall mortality was identi ed in patients treated with HCQ alone [26] .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, HCQ showed signi cant improvement in symptoms and radiological CT scan ndings [22] . One recent non-randomized study failed to demonstrate a bene t among patients hospitalized with an oxygen requirement A retrospective analysis of data from patients hospitalized with con rmed SARS-CoV-2 infection in all U.S. Veterans Health Administration medical centers until April 11, 2020 concluded that no clear evidence that the use of HCQ, either with or without azithromycin, reduced the risk of mechanical ventilation in patients hospitalized with COVID-19 [25]. An association of increased overall mortality was identi ed in patients treated with HCQ alone [26] .…”
Section: Discussionmentioning
confidence: 99%
“…We included 12 RCTs, 3 non-RCTs and 20 observational (including retrospective/prospective cohort, case-control) studies. Eighteen studies were from China, 10,11,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] six from USA, [47][48][49][50][51][52] five from Italy, [53][54][55][56][57] two from France 6,58 and one each from Brazil, 59 Hong Kong, 60 Spain 61 and Greece. 62 There was no significant difference in the mean age and sex distribution between any of the treatment and comparator groups included in our meta-analysis.…”
Section: Results From Clinical Studiesmentioning
confidence: 99%
“…Eight studies 6,10,31,32,[47][48][49]58 consisting of 3400 nCOV-2019 cases were included in the meta-analysis and were divided into two groups: 1522 subjects to hydroxychloroquine group and 1878 subjects to control group. Compared to the control group, hydroxychloroquine had an increased risk of having total adverse events (RR 1.82; 95% CI 1.57 to 2.12) and was associated with a longer time to clinical recovery (SMD 0.55; 95% CI 0.21 to 0.89).…”
Section: Hydroxychloroquine Vs Control Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have even reported both prophylactic and therapeutic advantages of CQ for SARS-CoV infection [7]. However, other researchers have reported in a retrospective study with no de ned administration time that no evidence in the use of hydroxychloroquine either with or without azithromycin reduced the risk of a mechanical ventilator in patients hospitalized with COVID-19 [8]. [9] in an open-label nonrandomized clinical trial concluded that hydroxychloroquine showed a signi cant association with viral load reduction/disappearance in COVID-19 patients, and its effect is reinforced by azithromycin.…”
Section: Discussionmentioning
confidence: 99%